Daddy, me, and the magic hour [book with audioplayer] - Melmed, Laura Krauss ([Library Ideas, LLC], 2020)
As twilight deepens, so does the bond between a little boy and his daddy. After getting home for the day and having dinner, a young boy is ready for some special time outside with his father. It's the Magic Hour, when the sun is going down and day meets night. As Daddy and son walk to the playground for some lively fun, they see their neighbors going through their evening rituals-watering plants, walking dogs, going for a run. As darkness sets in, Daddy and son quiet down and find fireflies, then make their way home to Mommy and bedtime.